2006
DOI: 10.1093/jnci/djj207
|View full text |Cite
|
Sign up to set email alerts
|

Extended Lung Cancer Incidence Follow-up in the Mayo Lung Project and Overdiagnosis

Abstract: The persistence of excess cases in the intervention arm after 16 additional years of follow-up provides continued support for overdiagnosis in lung cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
125
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(135 citation statements)
references
References 26 publications
5
125
0
5
Order By: Relevance
“…Quite unexpectedly, the 25-year followup of the Mayo trial showed that overall mortality was higher in the CXR arm compared with the standard care arm (difference not reaching statistical significance, P ¼ 0.09), even though the survival rate of lung cancer patients diagnosed at an early stage in the CXR arm was much higher (69 vs 54% at 5 years, median 16 years vs 5 years, respectively) (Marcus et al, 2006). These results confirmed the inefficacy of CXR monitoring, as well as the occurrence of overdiagnosis in the intervention arm.…”
Section: Previous Research Involving Other Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Quite unexpectedly, the 25-year followup of the Mayo trial showed that overall mortality was higher in the CXR arm compared with the standard care arm (difference not reaching statistical significance, P ¼ 0.09), even though the survival rate of lung cancer patients diagnosed at an early stage in the CXR arm was much higher (69 vs 54% at 5 years, median 16 years vs 5 years, respectively) (Marcus et al, 2006). These results confirmed the inefficacy of CXR monitoring, as well as the occurrence of overdiagnosis in the intervention arm.…”
Section: Previous Research Involving Other Modalitiesmentioning
confidence: 99%
“…Detection and treatment of slow-growing disease, also called overdiagnosis, represents one of the most likely explanations for the lack of mortality reduction observed in chest X-ray-screening trials, despite a significant increase in the overall resectability rate and proportion of stage I cancers in the intervention arm (Marcus et al, 2006). Overdiagnosis bias refers to the screening-related detection of cancers that would not have contributed to the death of the patient because of competing causes of death or because the lesion is indolent.…”
Section: Overdiagnosis Of Indolent Tumoursmentioning
confidence: 99%
“…The extended follow-up data for 16 years from the Mayo Lung Project, which demonstrate a persistent excess of cancers in the screened group compared with the control, suggest that overdiagnosis does occur. [44] However, it is uncertain to what extent it occurs in LC screening as reported rates vary widely (5 -51%). [45] Although it is a potentially harmful effect of screening, the current estimates available from LDCT trials suggest that the rate of overdiagnosis is relatively low (reported rate in the NLST was 18.5%, or 1.38 cases of overdiagnosis per 320 individuals needed to screen to prevent one LC death).…”
Section: Reviewmentioning
confidence: 99%
“…The clinical course of treated cancer patients all too often culminates in relapse and death. Ironically, growing evidence also suggests that many patients with premalignancy or even malignancy follow benign courses and die far more often of non-cancer causes than of cancer (3)(4)(5). These paradoxical phenomena form the dilemma of early detection-underdetection of life-threatening early disease and overdetection of indolent early disease.…”
mentioning
confidence: 99%
“…Morphology is the current standard for diagnosis of premalignant conditions and cancer itself, but morphologic assessment may be limited in its ability to distinguish asymptomatic indolent conditions from those that will progress to advanced malignancies and death (3)(4)(5)13). Examining cancer from an evolutionary perspective can open new approaches for cancer risk assessment, diagnosis, therapy and prevention.…”
mentioning
confidence: 99%